2015
DOI: 10.1111/ede.12111
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origin and status of two insect acetylcholinesterases and their structural conservation and differentiation

Abstract: Acetylcholinesterase (AChE) plays a pivotal role in synaptic transmission in the cholinergic nervous system of most animals, including insects. Insects possess duplicated AChE gene loci (ace1 vs. ace2) encoding two distinct AChEs (AChE1 and AChE2). A phylogenetic analysis suggested that the last common ancestor of two aces shared its origin with Platyhelminthes. In addition, the ace duplication event likely occurred after the divergence of Protostomian but before the split of Ecdysozoa. The ace1 lineage exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Since then, the presence of two ace s have been confirmed in many insect species, including the mosquitoes Culex pipiens 4 , Aedes aegypti 5 , Culex tritaeniorhynchus 6 , the aphids Myzus persicae 7 , Rhopalosiphum padi and Sitobion avenae 8 , the cockroach Blattella germanica 9 , the lepidopterans Helicoverpa assulta 10 , Plutella xylostella 11 , Chilo suppressalis 12 and Cnaphalocrocis medinalis 13 , the whitefly Bemisia tabaci 14 and the red flour beetle, Tribolium castaneum 15 , to name some of them. It was suggested that two ace genes may have originated from gene duplication before insect speciation 15, 16 . However, outside of mosquitoes, ace2 , but not ace 1, have been reported in the model insect Drosophila melanogaster and other Drosophila species.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the presence of two ace s have been confirmed in many insect species, including the mosquitoes Culex pipiens 4 , Aedes aegypti 5 , Culex tritaeniorhynchus 6 , the aphids Myzus persicae 7 , Rhopalosiphum padi and Sitobion avenae 8 , the cockroach Blattella germanica 9 , the lepidopterans Helicoverpa assulta 10 , Plutella xylostella 11 , Chilo suppressalis 12 and Cnaphalocrocis medinalis 13 , the whitefly Bemisia tabaci 14 and the red flour beetle, Tribolium castaneum 15 , to name some of them. It was suggested that two ace genes may have originated from gene duplication before insect speciation 15, 16 . However, outside of mosquitoes, ace2 , but not ace 1, have been reported in the model insect Drosophila melanogaster and other Drosophila species.…”
Section: Introductionmentioning
confidence: 99%
“…Signal peptides were predicted by the signalP program only in Bgace2 and Bnace2 . In ace1 ‐type and ace2‐ type AChEs, the ace2‐ specific region was clearly identified (Cha & Lee ) (Figure S1), and the genes were located on a phylogenetic tree (Figure S2). Based on this result, invertebrate AChE and vertebrate AChE, as well as butyrylcholinesterase (BChE), were divergent from the ancient common ancestral cholinesterase (ChE).…”
Section: Resultsmentioning
confidence: 99%
“…In insects, there are one or two AChE genes ( ace1, ace2 ), of which at least one plays a major role in the central cholinergic nervous system (Huchard et al . ; Kim and Lee ; Cha and Lee ). In Arachnida (e.g.…”
Section: Number Of Cholinesterase Genes In Animalsmentioning
confidence: 98%
“…A more thorough study determined that duplicated AChE genes in insects are under purifying selection and that some new specialization or essentiality appeared in the most divergent copy. Even though there are differences in the evolutionary rates of the two genes, the smallest value is not always associated with the gene that retained the main neuronal function (Cha and Lee ). However, carboxylesterases and AChE are rather large proteins and the number of amino acid residues crucial for the catalytic activity is limited (Sussman et al .…”
Section: Number Of Cholinesterase Genes In Animalsmentioning
confidence: 99%